The Effect of Consuming Edamame-Flavored Gummy with Jelutung Honey on The Management Of Stunting in Toddlers - Apriliana Pipin; Telly Katharina (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Stunting is a chronic nutritional problem that causes growth retardation in toddlers, negatively impacting physical and mental development, and long-term productivity. Preventing stunting is crucial, particularly during the first 1,000 days of life, by providing adequate nutrition. Edamame, which is a source of plant-based protein and essential micronutrients, and jelutung honey, which is rich in vitamins, minerals and antioxidants, have the potential to improve the nutritional status of stunted toddlers as an innovative solution. This quasi-experimental study was conducted in Sui Ambawang Village, involving stunted toddlers aged 1–5 years. The intervention involved consuming edamame gummies with a jelutung honey flavour enhancer for four weeks. Significant improvements in body weight (from 10.69 kg to 11.01 kg) and height (from 87.4 cm to 88.82 cm) were observed after the intervention (p=0.001). There was also a decrease in the percentage of toddlers categorised as undernourished and short. These results suggest that edamame gummies with jelutung honey could be an effective nutritional intervention for tackling stunting and could support the government's efforts to reduce stunting rates in Sui Ambawang Village.